Desain Motif Kontemporer Inspirasi Candi Jiwa Kabupaten Karawang dalam Produk Aksesori Fashion - Albahi, Haidarsyah Dwi (ATRAT: Jurnal Seni Rupa, 2025)
Indonesian cultural heritage is an inexhaustible source of inspiration for the creative industries, including fashion. However, many potential historical sites haven’t been fully explored. One such example is the Batujaya Temple complex in Karawang, specifically Candi Jiwa. Candi Jiwa, believed to be a relic from the pre-Tarumanegara kingdom era, has unique architectural characteristics: a minimalist brick structure with a lotus flower-shaped layout, which sets it apart from other temples in Java that are typically made of andesite stone with intricate reliefs. This research on contemporary motif design aims to (1) Identify the visual and philosophical elements of Candi Jiwa’s architecture; (2) Stylize the architectural forms of Candi Jiwa into a motif design; and (3) Apply the resulting contemporary motifs to fashion accessory products. The design methods used include a literature study, visual observation, sketch exploration, form stylization, digitalization, and product mock-up creation. The result of this design process is a series of primary and derivative motifs inspired by the layout, structure, and texture of Candi Jiwa. These motifs were then digitally applied as mock-ups on accessory products such as scarves, vests, hijabs, and tote bags. This design project demonstrates that the simplicity and uniqueness of Candi Jiwa’s form have great potential to be translated into modern, ethnic motif designs with a strong narrative value.